Quantum coherent control in pulsed waveguide optomechanics for photon-phonon entanglement via Brillouin scattering - Zhu, Changlong; Zhang, Junyin; Wolff, Christian; Stiller, Birgit (2023 Conference on Lasers and Electro-Optics Europe and European Quantum Electronics Conference, CLEO/Europe-EQEC 2023, 2023)
Brillouin optomechanics provides a way to coherently control traveling acoustic excitations in waveguides system, which enables the manipulation and processing of classical and quantum information. Although Brillouin optomechanics has been largely investigated in the steady-state regime using continuous waves [1-3], waveguide experiments are often realized by using optical pulses for example for Brillouin-based memory [4,5]. This requires a dynamic framework treatment for the temporal domain including the noise dynamics.
CRIS-Team Scopus Importer:2024-12-16